Exclusion and coordination in collaborative innovation and patent law. (6th February 2009) - Lee, Nari
Intellectual property law has been criticised for over-arching scope of protection and at the same time, for insufficient protection. This seeming contradiction may stem from the discrepancies between the actual innovation practice and process and the models adopted in law. This paper illustrates this contradiction in the patent laws' treatment of collaborative innovators. Particularly, this study examines how the participation of multiple innovators at the initial stage of the innovation is regulated under the patent laws in the US, Japan and, to an extent, in Europe. A single entity perspective and a concurrent closed invention model implied in law create legal uncertainties for collaborative innovators. This brings forward the organisational capability that provides inter- and intra-firm governance structure over the innovative process and the uses of innovation in managing the uncertainties before, during and after collaboration. This capability is in a central role in addressing the seeming contradiction.